2017
DOI: 10.1111/dom.12933
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of sitagliptin as compared with glimepiride in Japanese patients with type 2 diabetes mellitus aged ≥ 60 years (START‐J trial)

Abstract: The aim of this study was to evaluate the efficacy and safety of sitagliptin administered to elderly patients with type 2 diabetes mellitus (T2DM) for 1 year as compared with glimepiride. Patients aged ≥60 years with T2DM and inadequately controlled blood glucose were randomly assigned to sitagliptin 50 mg once daily or glimepiride 0.5 mg once daily for 52 weeks. The primary efficacy endpoint was the change in glycated haemoglobin (HbA1c) from baseline to week 52. Secondary efficacy endpoints included self‐mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 14 publications
2
28
0
Order By: Relevance
“…The results of the safety analysis demonstrate that sitagliptin is generally well tolerated with routine long-term use. Overall, ADRs occurred at a relatively low frequency in this PMS and the overall frequency of ADRs of special interest during the observation period (0.86% of patients) is consistent with the results of previous clinical trials of sitagliptin in Japanese patients, in which the frequency of serious ADRs was typically less than 1.0% [ 15 , 17 19 , 22 , 23 ]. In accordance with the known safety profile of sitagliptin, hypoglycaemia was the most common specific ADR noted with long-term use.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The results of the safety analysis demonstrate that sitagliptin is generally well tolerated with routine long-term use. Overall, ADRs occurred at a relatively low frequency in this PMS and the overall frequency of ADRs of special interest during the observation period (0.86% of patients) is consistent with the results of previous clinical trials of sitagliptin in Japanese patients, in which the frequency of serious ADRs was typically less than 1.0% [ 15 , 17 19 , 22 , 23 ]. In accordance with the known safety profile of sitagliptin, hypoglycaemia was the most common specific ADR noted with long-term use.…”
Section: Discussionsupporting
confidence: 90%
“…Dipeptidyl peptidase 4 (DPP4) inhibitors prolong the effect of incretin hormones [especially glucagon-like peptide 1 (GLP-1) and glucose-dependent insulinotropic polypeptide (GIP)] in stimulating insulin release and decreasing glucagon secretion in a blood glucose-dependent manner. DPP4 inhibitors have demonstrated sufficient efficacy in lowering blood glucose with a lower risk of hypoglycaemia compared with other insulin secretagogues such as sulfonylureas [15]. Owing to their well-balanced benefit to risk characteristics, DPP4 inhibitors are currently the most commonly prescribed oral hypoglycaemic agents in Japan [16].…”
Section: Introductionmentioning
confidence: 99%
“…A high P/I ratio suggests that there is a high proportion of proinsulin (pre-stage peptide of insulin) among the secreted insulin, which may indicate beta-cell dysfunction. Recently, Terauchi et al reported that sitagliptin exhibited a lowering effect on P/I, whereas glimepiride had no such effect in Japanese elderly type 2 diabetes patients [8]. Although this head-to-head comparison between 0.5 mg glimepiride and 50 mg sitagliptin for 52 weeks highlighted the usefulness of both drugs in elderly type 2 diabetes patients, our results further suggest benefits associated with combination of low doses of SU and DPP4 inhibitors, which could achieve marked reduction without serious hypoglycemia and may protection beta-cells.…”
Section: Discussionmentioning
confidence: 99%
“…These results are in support of a study mentioning that a significant decrease was noted in mean blood glucose levels in patients who were treated with combination of sitagliptin+metformin and glimepiride alone. [15][16][17] When comparing the glycemia control achieved by combination therapy of sitagliptin+metformin a statistically significant difference was recorded among mean blood glucose levels for a period from zero month to six month. A significant difference (P<0.001) was noted in when HbA1c compared after starting the treatment with HbA1c recorded on Zero month treatment in group A who were treated with sitaglitin+metformin.…”
Section: Discussionmentioning
confidence: 99%
“…These results are in accordance to a study mentioning the significant decrease in HbA1c values in patients treated with glimepiride alone. 17 While comparing the incidence adverse drug reactions less number of hypoglycaemic episodes were recorded in patients who were treated with sitagliptin+metformin combination.…”
Section: Discussionmentioning
confidence: 99%